Age-Related Disease Burden in China, 1997–2017: Findings From the Global Burden of Disease Study - Hu, Dan; Yan, Wu; Zhu, Jing; Zhu, Ying; Chen, Jiaying (Frontiers in Public Health, 2021)
Background: The population is aging much faster in China than other low- and middle-income countries. With the accelerated aging of the population, incidence and disease burden of age-related diseases have also continued to increase. Exploring the burden of age-related diseases is crucial for early disease prevention, assessing the extent of population aging, and achieving the goal of healthy aging. Methods: We used the dataset from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD), and selected data on incidence, prevalence, and disease burden in China, in 1997, 2007, and 2017. We classified age-related diseases, which were defined as diseases in which the incidence rate increased quadratically with age in the adult population. Additionally, we described the changes in age-related diseases during the study period by different GBD categories. It also measured changes in the age-related disease burden in our study period, including disability-adjusted life years (DALY), years of life lost (YLL), and years lived with disability (YLD). Finally, we compared the differences in the age-related disease burdens for men and women. Results: Among the 293 diseases listed in the GBD study, 69 in 2017, 78 in 1997 and 72 in 2007 were identified as age-related diseases. More than half of the age-related diseases belonged to non-communicable diseases (NCDs) in our study period. The rate of age-standardized age-related disease burden decreased between 1997 and 2017. DALYs decreased by 24.89% for non-age-related diseases and by 50.15% in age-related diseases from 1997 to 2017. The age-related disease burden of men was higher than that of women; we found a decreasing trend, with −46.23% in men and −54.90% in women. Conclusions: Comparing characteristics of the aging population in China and the world, we found that China does not have the typical disease characteristics of aging society. Currently, China faces the dual threat of NCDs and communicable diseases, and NCDs account for the vast majority of the age-related disease burden. Our health systems should focus on disease prevention and early detection among the entire population, instead of treatment. Further studies should focus on reducing the duration and severity of morbidity in later life.